Investigation of the Dalitz decays and the electromagnetic form factors of the eta and pion-meson - Berghäuser, Henning; Justus Liebig University Giessen (My University, 2010)
In this thesis the Dalitz decays of the pion, eta and omega-meson have been studied in photon induced reactions off the proton. The main aim has been to determine the electro-magnetic transition form factor of the eta-meson. This form factor provides significant information about the electromagnetic properties of this meson. As a meson is a non-point like particle, the corresponding electro-magnetic transition form factor is expected to differ from the standard QED prediction (Quantum Electro Dynamics). Hence, a measurement of this form factor provides the possibility to investigate this deviation from the QED and to test theoretical models like the (Vector Meson Dominance Model) VMD or the model by Leupold-Terschluesen.Beside the Dalitz decays other decay modes of the eta and the omega-meson were analyzed and the branching ratios of the decays eta->pi+pi-pi0, eta-Dalitz and omega->gamma+pion were determined. Furthermore the cross section of -production as well as the cross section of pion-eta-production in photon induced reactions off the proton were determined. Another aspect of this work was to investigate the possibility of separating electrons and positrons from charged pions with the Crystal Ball and TAPS detector systems at MAMI-C in Mainz. This coupled detector-setup is very efficient in detecting photons and thus it is particularly suited for measure-ments of neutral decay modes of hadrons. As this setup does not use a magnetic field, an accurate separation of electrons/positrons from charged pions is difficult. However, it was shown in this work, that an accurate separation and identification of those particles is possible by exploiting the full kinematic information available in ex-clusive analyses. Thereby Dalitz decays were identified. The background from charged pions was suppressed further. Moreover it was found that cuts on the cluster sizes of the charged hits further suppress the charged pion background. The pro-bability for the misidentification of a charged pion-pair as an electron/positron-pair is less than 3 10^(-7).The experimental data were taken during two beamtimes in 2007 at the electron acceleration facility MAMI-C in Mainz. Energy tagged photons pro-duced via the bremsstrahlung process impinged on a liquid hydrogen target and induced among others the reactions of interest. The detectors Tagger, Crystal Ball (including the PID) and TAPS (including the VETO) were used for data recording. A preliminary particle identification was provided by the dE-versus-E and the time-of-flight method. Furthermore the information about time-coincidences between detected hits were exploited in order to suppress random events. The total amount of experimental raw data was approximately 2 TByte. Therefore a compression of the data was necessary. For this purpose a ntuple-based analysis procedure was developed. Only events fulfilling certain requirements were saved to these ntuples. Thus the original amount of data was significantly reduced. Before this compression, the data had been calibrated by the A2-group of the University of Giessen. In this respect many procedures, macros and programs had to be developed from scratch. The same holds for the subsequent analysis of the data. A new analysis program called AR2v3 was developed in C++. In all analyses the detection of the meson and the recoiling proton was required; thus the full kinematic information could be exploited. Cuts were applied on the energy balance, momentum balance, missing mass and the coplanarity. Depending on the particular decay channel further cuts were applied on the relative angle between particles, the incident energy, the -angle of the proton and if applicable on the cluster sizes of the charged hits. The applied cuts were verified by displaying each variable under the constraint of all other cuts. Besides the analysis of experimental data sim-ulated data were analyzed in order to determine the detector response. The simulated data were produced by a Monte-Carlo simulation which contained the full detector setup. The corresponding start distributions for the simulation were generated using a phase space event generator as well as the PLUTO event generator. In the exclusive analysis of the eta-Dalitz decay 827 events were reconstructed. This is an improvement by a factor 8 with respect to the measurement by the SND collaboration. The slope parameter of the associated transition form factor was determined asb = dF/dq2 |q2=0 = Lambda^(-2) = (1.84 + 0.43 − 0.32) GeV^(-2)with: Lambda = (740 +/- 74) MeVWithin the errors this result is consistent with the result of the Lepton-G experiment, the NA60 experiment, and the SND experiment. Furthermore the result agrees within the errors with the theoretical prediction of.In the investigation of the pion-Dalitz analysis no deviation from the QED-pre-diction was found. In the case of the omega-Dalitz decay a from factor could not be determined because of limited statistics.The determined branching ratios are: BR_Dalitz = (6.18 +/- 0.65) 10^(-3) BR_Eta->Pi+Pi-Pi0 = (22.9 +/- 1.7)% BR_Omega->GammaPion = (10.2 +/- 1.4)%These results are consistent with the values in the Particle Data Booklet of the Particle Data Group. Furthermore the obtained cross sections for eta-production and for pion-eta-production are in agreement with the results of former publications.

Mit dem CB/TAPS-Experiment am Elektronenbeschleuniger MAMI-C in Mainz werden Zerfälle von Mesonen und Baryonen untersucht. Die Hadronen werden in photoninduzierten Reaktionen an Protonen (und Neutronen) produziert. Dabei können als Target nicht nur freie Protonen (flüssig Wasserstoff) sondern auch Atomkerne (Niob, Kohlenstoff, Blei) verwendet werden. In der vorliegenden Arbeit wurden die Dalitz Zerfälle des Eta und des neutralen Pion-Mesons analysiert. Der Fokus lag dabei auf der Bestimmung des elektromagnetischen Übergangsformfaktors des Eta-Mesons. Dieser Formfaktor enthält wesentliche Informationen über die elektro-magnetischen Eigenschaften und Substrukturen des Teilchens. Mesonen sind keine punktförmigen Elementarteilchen, sondern bestehen aus stark wechsel-wirkenden Quarks und Antiquarks. Demzufolge sind für die elektromagne-tischen Zerfälle eines Mesons Abweichungen von den Vorhersagen der Quanten Elektrodynamik (QED) zu erwarten. Für diese Abweichungen exis-tieren Vorhersagen unterschiedlicher theoretischer Modelle, wie z.B. dem Vector Meson Dominance Model (VMD) oder dem Leupold-Terschluesen Modell. Anhand von Experimenten wie in dieser Arbeit können die theoretischen Modelle überprüft werden.Neben den Dalitz Zerfällen wurden in der vorliegenden Arbeit weitere Zerfalls-kanäle der Mesonen Eta und Omega untersucht mit dem Ziel, die entsprechenden Verzweigungsverhältnisse zu bestimmen. Darüber hinaus wurde der Wirkungsquerschnitt für die Pion-Eta-Produktion am Proton bestimmt.Ein weiterer Aspekt dieser Arbeit war die Entwicklung einer Methode zur Separation von geladenen Pionen und Elektronen/Positronen im Rahmen der Teilchenidentifikation. Diese Trennung ist eine wesentliche Voraussetzung für die Analyse geladener Zerfallskanäle. Da das CB/TAPS Experiment kein Magnetfeld verwendet, erscheint diese Separation zunächst als sehr schwierig. Jedoch wird in dieser Arbeit eine Methode vorgestellt, mit der eine Separation auch ohne ein Magnetfeld erfolgreich realisiert werden kann. Werden alle Teilchen im Endzustand einer Reaktion sowie das Rückstoßproton nach-gewiesen (exklusive Analyse), so können alle Informationen der vollständigen Kinematik in der Analyse ausgenutzt werden, um missidentifizierte geladene Pionen zu entfernen. Zusätzliche Schnitte auf die Clustergrößen helfen ebenfalls diesen Untergrund weiter zu unterdrücken. Die Wahrscheinlichkeit dafür, ein geladenes Pion-Paar als Elektron/Positron-Paar falsch zu identifizieren ist kleiner als 3 10^(-7). Die experimentellen Daten wurden in zwei Strahlzeiten in 2007 mit den Detektoren Tagger, Crystal Ball und TAPS aufgezeichnet. Der primäre Photon-enstrahl, der über den Bremsstrahlungseffekt aus dem Elektronenstrahl von MAMI-C erzeugt wurde, traf auf ein Flüssigwasserstofftarget auf und induzierte dabei die hadronischen Reaktionen.Eine vorläufige Teilchenidentifikation wurde mit Hilfe der dEvE-Methode und der time-of-flight-Technik realisiert. Anhand der gemessenen Zeitkoinzidenzen konnten zufällige Ereignisse aussortiert werden. Da der Umfang der experimen-tellen Daten ca. 2 TByte betrug, war eine Datenkompression notwendig. Für deren Verwirklichung wurde eine spezielle, Ntuple-gestützte Analyseprozedur entwickelt und nur solche Ereignisse wurden ausgewertet, die bestimmte Kriterien erfüllten. Auf diese Weise konnte die Datenmenge stark reduziert werden. Neben der Kompression wurde auch die Kalibration der Daten und die vorangehende Entwicklung dazu geeigneter Methoden und benötigter Program-me an der Universität Giessen durchgeführt. Auch für die Analyse der detek-tierten Ereignisse wurde ein neues Programm in C++ entwickelt (AR2v3). In der exklusiven Analyse des Eta Dalitz Zerfalls konnten 827 Ereignisse rekonstruiert werden. Verglichen mit dem Ergebnis der SND-Kollaboration ist damit die Statistik in der vorliegenden Arbeit um einen Faktor 8 größer. Für die Steigung des η-Formfaktors wurde der folgende Wert ermittelt:b = dF/dq^2(|q=0) = Lambda^(-2)= (1.84 + 0.43 − 0.32) GeV^(-2)mit: Lambda = (740 +/- 74) MeVInnerhalb der Fehler stimmt dieses Ergebnis mit den Resultaten der Experi-mente Lepton-G, NA60 und SND überein. Des Weiteren konnte eine gute Über-einstimmung mit dem theoretischen Modell von Leupold-Terschlüsen festge-stellt werden. In der Analyse des Pion-Dalitz Zerfalls wurde wie erwartet keine Abweichung von der QED-Vorhersage gefunden. Neben den genannten Dalitz-Zerfällen wurden auch die Reaktionen Eta->2Gamma, Eta->2GammPion, Eta->3Pion, Eta->Pi+Pi0Pi0, Omega->Pi+Pi0Pi0 sowie Omega->GammaPion untersucht. In diesem Zusammenhang konnten die folgenden Verzweigungs-verhältnisse bestimmt werden: BR_DalitzDalitz = (6.18 +/- 0.65) 10^(-3) BR_Eta->Pi+Pi0Pi0 = (22.9 +/- 1.7)% BR_Omega->Pi0Gamma = (10.2 +/- 1.4)%Diese Ergebnisse stimmen mit publizierten Resultaten anderer Experimente überein. Es ist anzumerken, dass der Fehler des in dieser Arbeit gemessenen Wertes für BR_Dalitz kleiner ist als der entsprechende Fehler im Particle Data Booklet der Particle Data Group.
Untersuchung von Dalitz Zerfällen und Bestimmung der Übergangsformfaktoren des Eta- und des Pion-Mesons
Keywords: Übergangsformfaktoren; Eta; Pion; Dalitz Zerfall; transition form factors; eta; pion; Dalitz decays; ddc:530